Clinical Presentation and Disease Course of 37 Consecutive Cases of Progressive Multifocal Leukoencephalopathy (PML) at a German Tertiary-Care Hospital: A Retrospective Observational Study - Lisa M. Graf; Sina C. Rosenkranz; Sina C. Rosenkranz; Angelique Hölzemer; Angelique Hölzemer; Angelique Hölzemer; Christian Hagel; Einar Goebell; Sabine Jordan; Sabine Jordan; Manuel A. Friese; Marylyn M. Addo; et al. (Frontiers in Neurology, 2021)
Background: Progressive multifocal leukoencephalopathy (PML) caused by JCV is a rare but frequently fatal disease of the central nervous system, usually affecting immunocompromised individuals. Our study aims to expand the data on patient characteristics, diagnosis, clinical course, possible PML-directed treatment, and outcome of patients with PML at a German tertiary-care hospital.Methods:In this single-center observational cohort study, 37 consecutive patients with a confirmed diagnosis of PML seen at the University Medical Center Hamburg-Eppendorf from 2013 until 2019 were retrospectively analyzed by chart review with a special focus on demographics, risk factors, and clinical aspects as well as PML-directed treatment and survival.Results:We identified 37 patients with definite, probable, and possible PML diagnosis. 36 patients (97%) had underlying immunosuppressive disorders such as HIV/AIDS (n = 17; 46%), previous treatment with monoclonal antibodies (n = 6; 16%), hematological or oncological malignancies (n = 6; 16%), sarcoidosis (n = 5; 14%), solid organ transplantation (n = 1; 3%), and diagnosis of mixed connective tissue disease (n = 1; 3%). In only one patient no evident immunocompromised condition was detected (n = 1; 3%). Treatment attempts to improve the outcome of PML were reported in 13 patients (n = 13; 35%). Twenty seven percent of patients were lost to follow-up (n = 10). Twenty four-month survival rate after diagnosis of PML was 56% (n = 15).Conclusion: This interdisciplinary retrospective study describes epidemiology, risk factors, clinical course, and treatment trials in patients with PML at a German tertiary-care hospital. Acquired immunosuppression due to HIV-1 constituted the leading cause of PML in this monocenter cohort.